Treatment of atypical pacemaker‐mediated tachycardia with ablation of the retrograde atrioventricular nodal pathway. (9th March 2020) - Shelton, Richard; Cho, Jae H.; Joshi, Shreel; Betzold, Robert; Shehata, Michael; Ehdaie, Ashkan; Swerdlow, Charles
Abstract: A 25‐year‐old runner received a single‐lead, VDD pacemaker after ablation of AV nodal reentrant tachycardia complicated by intermittent AV block. The rate‐adaptive AV delay algorithm (RAAV), which shortens the sensed AV interval (SAV) at faster atrial rates, was programmed to provide a physiologic SAV with exercise. She developed repetitive, atypical, long‐RP pacemaker‐mediated tachycardia (PMT) because the RAAV shortened the antegrade SAV and retrograde conduction occurred over the slow AV nodal pathway. PMT was refractory to usual programming solutions. Using high‐density electroanatomic mapping, we were able to ablate the retrograde limb of PMT without further damaging AV conduction.